Fenomenologi Personal Branding Cosplayer: Studi Desain Komunikasi Visual dan Media Sosial - Edy Chandra; Nero Devanca Chandra (LPPM STIKI Malang, 2025)
Cosplay has evolved as both a form of identity expression and a personal branding strategy in the digital era. This study examines the phenomenology of cosplayer personal branding through a Visual Communication Design approach, highlighting the role of social media in identity formation and maintenance. This research is part of Edy Chandra's study entitled